154k views
5 votes
Follow the steps to solve this equation. 3(2x + 6) – 4x = 2(5x – 2) + 6. solve for x

User Fukudama
by
5.2k points

2 Answers

2 votes

Answer: x=2

Explanation:

Did it on edge

User Mike Minutillo
by
4.1k points
3 votes

Answer:

x = 2

Explanation:

3(2x + 6) – 4x = 2(5x – 2) + 6

Distributive property

6x + 18 - 4x = 10x - 4 + 6

Combine like terms

2x + 18 = 10x + 2

Subtract 10x from both sides

-8x + 18 = 2

Subtract 18 from both sides

-8x = - 16

Divide both sides by -8

x = 2

User Thomas Denney
by
5.6k points